Non-photochemical quenching in epipsammic and epipelic microalgal assemblages from two marine ecosystems. (15th March 2017) - Pniewski, Filip F.; Richard, Pierre; Latała, Adam; Blanchard, Gerard
Abstract: This work presents differences in the non-photochemical quenching of chlorophyll fluorescence (NPQ) formation and its further dark relaxation between two microphytobenthos types, i.e. epipelon from Aiguillon Bay on the Atlantic coast and epipsammon from Puck Bay in the Baltic Sea. NPQ was characterized by the induction kinetics and light-response curves subsequently compared to the light-response curves of PSII relative electron transport rate (rETR), measured on assemblages collected in summer (July/August) and autumn (October/November). Both assemblages differed in species composition. Epipelon was exclusively composed of motile bi-raphid diatoms, while in epipsammon next to small-sized diatoms species other taxonomic groups such as green algae, euglenophytes and blue-green algae were also present. The study confirmed that epipelon was low light acclimated, while epipsammon showed features of high light acclimation. In both assemblage types a clear seasonal shift in photoprotection capacity was observed. Higher NPQ values were always observed in summer. In epipelon, the maximum NPQ (NPQmax ) inferred from the NPQ light-response curves reached the value above 11; in epipsammon, NPQmax was up to the value of 4. The NPQ induction kinetics together with the light stress-recovery analysis suggested the presence of different photoprotective mechanisms in the studied microphytobenthos communities. In epipsammon photoprotection was assumed to be mostly dependent on the activity of the xanthophyll cycle, while in epipelon other processes also contributed to the overall photoprotection. Neither epipelon nor epipsammon showed compelling signs of photoinhibition. By comparing the NPQ and rETR light-response curves it was shown that in high light acclimated epipsammon NPQ promptly responded to changes in light conditions. A weak relationship between NPQ development and photochemistry emphasized the importance of behavioural photoprotection in low light acclimated epipelon. Overall, both assemblage types developed different, yet effective, photoprotection strategies and the main differences resulted from their taxonomic composition and photoacclimation status. Highlights: Non-photochemical quenching in epipelic and epipsammic assemblages was examined. Differences in the NPQ capacity, induction kinetics and dark relaxation were found. The contribution of NPQ components differed between assemblages. In both assemblage types no photoinhibition was observed. Species composition and photoacclimation status caused the observed variability.